Climate and sea-level controls on turbidity current activity on the Tanzanian upper slope during the last deglaciation and the Holocene. (1st February 2016) - Liu, Xiting; Rendle-Bühring, Rebecca; Henrich, Rüdiger
Abstract: Turbidity current is one of the most important mechanisms for rapid transportation of terrigenous sediments from the continental margin to the deep sea. Although extensive work on turbidite systems has been carried out globally, the Tanzanian margin, off East Africa, is poorly understood. This paper will therefore use a well-dated high-resolution marine core (GeoB12624-1), obtained during RV Meteor Cruise M75/2, from the upper Tanzanian continental slope, offshore the Rufiji River delta, to demonstrate which environmental parameters, e.g., climate versus sea level, control the temporal distribution of the turbidite deposits during the last deglaciation and the Holocene. Results show that the turbidite deposits are composed of coarser-grained sediments with normally graded bedding. The thickness, mean grain size and frequency of the turbidite beds were estimated to detect turbidity current activity since the Last Glacial Maximum (LGM). A total of 12 turbidite beds (TI-T12) was recognized and divided into three intervals, based on the presence and intensity of the turbidite deposits. (I) a glacial sea-level lowstand (LGM and Heinrich Stadial 1; 19.3–14.6 ka): suppressed turbidity current activity due to arid conditions in the hinterland and sea-level lowstand. (II) A deglacial sea-level rise period (Bølling-Allerød interval to the early Holocene; 14.6–8 ka): turbidity current activity started to be strengthened during the Bølling-Allerød warming interval (T1), followed by a first increase in turbidite frequency, thickness and mean grain-size during the Younger Dryas (T2–T4) and a second increase during the early Holocene (T5–T10). (III) An interglacial sea-level highstand period (mid-to late Holocene; 8–2.5 ka): turbidity current activity diminished from the mid- (T11, T12) to late Holocene. This temporal distribution of turbidite deposits indicates that turbidity currents were most active during the last sea-level rise, synchronous with more humid climate in the hinterland, than during a sea-level lowstand (e.g., LGM) when climate was more arid. Thus, we propose that it is the climate conditions in the hinterland that form the primary controlling factor for turbidity current activity of Tanzanian slope. The remobilization of lowstand sediments on the Tanzanian continental margin during a sea-level rise, combined with shedding sediments towards the study area from the main canyon/channel, also plays a role in supplying new sediments to the turbidite system. These new data demonstrate that, in specific continental margin, high fluvial discharge will promote sediment transfer along the shelf and slope even during sea-level rise and highstand. Highlights: We present a high-resolution sedimentary record off Tanzania since the LGM. Turbidity currents were most active during the sea-level rise and highstand. The temporal distribution of the turbidite deposits correspond humid climate.